2021
DOI: 10.3847/1538-3881/abfdad
|View full text |Cite
|
Sign up to set email alerts
|

Disequilibrium Chemistry in Exoplanet Atmospheres Observed with the Hubble Space Telescope

Abstract: Literature on the theory of exoplanet atmospheric disequilibrium chemistry is rich, although its observational counterpart has yet to emerge beyond the hints provided by a few targets in dedicated studies. We report results from an uniform data reduction and analysis for a catalog of 62 Hubble Space Telescope exoplanet transit spectra where we assess the atmospheric model preference for disequilibrium chemistry (i.e., water vapor is not the dominant absorption spectral signature) over thermal equilibrium chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Since the last two groups return similar results, we choose to calculate A H using reduced data from Mugnai et al (2021), which is also close to the A H calculated from Libby-Roberts et al (2021). A trend study using uniform data reduction methods would be preferred, allowing for more rigorous comparison between exoplanets intrinsic properties (e.g., Sing et al 2016;Tsiaras et al 2018;Roudier et al 2021). At present, we choose reduced data from the more recently published works, which either incorporate data from more recent transit observations (e.g., HD 97658 b we use Guo et al 2020instead of Knutson et al 2014a or use more up-to-date stellar parameters (e.g., K2-18b we use Benneke et al 2019ainstead of Tsiaras et al 2019.…”
Section: Transmission Data Reductionmentioning
confidence: 99%
“…Since the last two groups return similar results, we choose to calculate A H using reduced data from Mugnai et al (2021), which is also close to the A H calculated from Libby-Roberts et al (2021). A trend study using uniform data reduction methods would be preferred, allowing for more rigorous comparison between exoplanets intrinsic properties (e.g., Sing et al 2016;Tsiaras et al 2018;Roudier et al 2021). At present, we choose reduced data from the more recently published works, which either incorporate data from more recent transit observations (e.g., HD 97658 b we use Guo et al 2020instead of Knutson et al 2014a or use more up-to-date stellar parameters (e.g., K2-18b we use Benneke et al 2019ainstead of Tsiaras et al 2019.…”
Section: Transmission Data Reductionmentioning
confidence: 99%
“…Detection of clouds and hazes is typically done through measuring the degree of spectral modulation (Sing et al 2016), which can then be compared to estimates of the theoretical possible values (Iyer et al 2016;Gao et al 2020) or plotted against various physical parameters to search for correlations (Stevenson 2016;Fu et al 2017;Gao et al 2020;Dymont et al 2021). Here, we perform this analysis using the catalog from Roudier et al (2021) that consists of 62 planets observed with the WFC3 instrument onboard the HST using the G141 infrared (IR) grism (1.1-1.6 µm) spatial scan observations. Compared with previous works, this exoplanet catalog has three important advantages for the study of clouds.…”
Section: Methodsmentioning
confidence: 99%
“…A key motivation for a robust IM is the application to comparative planetology, and this IM can provide uniform estimation of spectrum across a large number of targets. A large scale analysis using the same IM and estimation methodology presented in this paper is performed in Roudier et al (2021). Analyses like this referenced one, can benefit from applying the IM analysis techniques employed in this paper, and specific metrics such as RSDSN can be used to flag targets in the set that might not conform to the IM assumptions.…”
Section: Application To Comparative Planetologymentioning
confidence: 99%